Evolution of Yeast Populations during Different Biodynamic Winemaking Processes - Guzzon, R.; Widmann, G.; Settanni, L.; Malacarne, M.; Francesca, N.; Larcher, R. (South African Journal of Enology and Viticulture, 2011)
This work was performed to evaluate the evolution of indigenous yeasts during wine productions carried out following the principles of biodynamic agriculture. Five trials were designed with different technological interventions consisting of the addition of nitrogen (in the form of ammonium salt), thiamine salt, oxygen, and pied de cuvée at varying concentrations. Yeasts were estimated by haemocytometer chamber and plate counts and identified by sequencing of the D1/D2 domain of the 26S rRNA gene. The isolates identified as Saccharomyces cerevisiae were found to dominate must fermentations and were genetically differentiated by interdelta sequence analysis (ISA). Several non-Saccharomyces species, in particular Hanseniaspora spp. and Candida spp., were found at subdominant levels during must fermentation. The trial added with both nitrogen and thiamine (NTV) showed the highest fermentation rate and microbial richness. The internal surfaces of the cellar equipment were characterised by a certain yeast biodiversity and hosted the species found during winemaking; the wooden surfaces represented the primary source of inoculation of a strain of S. cerevisiae found dominant in all winemaking trials.